Highly efficient luminescent side-chain polymers with short-spacer attached tetraphenylethylene AIEgens via RAFT polymerization capable of naked eye explosive detection. Issue 30 (19th July 2018) - Li, Qian; Li, Xiao; Wu, Zhongying; Sun, Yuhao; Fang, Jianglin; Chen, Dongzhong
Abstract : The fluorescence quantum yield of side-chain AIE polymers was remarkably promoted just by shortening the linking spacer. Abstract : Tetraphenylethylene (TPE) is one of the well-known typical aggregation-induced emission (AIE) luminogens (AIEgens) and TPE-containing polymers possess excellent processing properties which facilitates the fabrication of various AIE systems and devices. For AIE active side-chain polymers, increasing the fluorescence quantum yield through suitable molecular design is very appealing. In this work, we present the well-controlled synthesis of a series of TPE polyacrylate side-chain polymers of Pm with short spacers with methylene number m = 0–5 via RAFT polymerization. All the obtained polymers exhibit typical and strong AIE characteristics in THF/H2 O solution mixtures and in solid state films. In particular, greatly enhanced fluorescence emission is achieved with reduced spacer lengths, and further significant improvement achieved through annealing, which is ascribed to the restriction of intramolecular motions (RIM) and the blocking of the non-radiative channels due to overcrowding and confinement thanks to the strong positive coupling effect and the jacketing effect of side-chain polymers with very short spacers. The quantum yields of 34.4%, 32.0% and 31.4%, respectively, for the polymer films P 0, P 1 and P 2 are several times higher than those of homologous polymers with longer spacers reported in the literature. Based on these TPE side-chain polymers of very short spacers, a simple, economic and visual method for detection of the explosive 2, 4, 6-trinitrotoluene (TNT) is demonstrated. Therefore, a facile approach and feasible strategy of simply adopting very short spacers for side-chain AIE active polymer preparation to significantly enhance the luminescence efficiency has been properly established and proposed, which may provide guidance and have a wealth of implications for the rational design and preparation of highly efficient luminescent AIE polymer materials.